PENGARUH GAYA KEPEMIMPINAN DAN INSENTIF DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL INTERVENING TERHADAP KINERJA KARYAWAN - FEBRIANTI, INDRI; SYAHRIAN, SYAHRIAN (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This study aims to examine how the influence of leadership style and incentives with organizational culture as an intervening variable on the performance of employees of PT. XYZ. The sample used in this study was 80 permanent employees who had worked for more than one year at PT. XYZ. The sampling method used in this study is the purposive sampling method with the data analysis method used is the SEM (Structural Equation Modeling) method. The results obtained in this study show that leadership style, incentives and organizational culture have an influence on the performance of employees of PT. XYZ. Leadership style and incentives have an influence on the organizational culture of PT. XYZ. Organizational culture mediates the relationship between the leadership style and employee performance of PT. XYZ. Organizational culture mediates the relationship between incentives and employee performance of PT. XYZ. The application of this study is suggested to PT. XYZ must increase attention to leadership, incentives, and organizational culture so that the performance of PT. XYZ can get better.